Endothelin-1 receptors play a minor role in the protection against acute Trypanosoma cruzi infection in mice - Roffê,E. (2007)
Chagas' disease, caused by the protozoan Trypanosoma cruzi, is a major cause of cardiovascular disability in countries where it is endemic. Damage to the heart microvasculature has been proposed to be an important factor in the pathogenesis of heart dysfunction. Endothelin-1 (ET-1) is a potent vasoconstrictor and exerts its effects via specific ET A and ET B receptors. A few studies have suggested a role for ET-1 and its receptors in the pathogenesis of Chagas' disease. We investigated the effects of treatment with bosentan, an ET A/ET B receptor antagonist, on the course of T. cruzi infection (Y strain) in C57Bl/6 mice. Treatment with bosentan (100 mg kg-1 day-1) was given per os starting day 0 after infection until sacrifice. Bosentan significantly increased myocardial inflammation, with no effects on parasitemia. Although the total number of nests was similar, a lower number of intact amastigote nests was found in the heart of bosentan-treated animals. Bosentan failed to affect the infection-associated increase in the cardiac levels of the cytokines IFN-g and TNF-a and the chemokines CCL2/MCP-1, CCL3/MIP-1a and CCL5/RANTES. In vitro, pre-incubation with ET-1 (0.1 µM) 4 h before infection enhanced the uptake of the parasites by peritoneal macrophages, and this effect was abrogated when macrophages were pre-treated with bosentan (1 µM) 15 min before incubation with ET-1. However, ET-1 did not alter killing of intracellular parasites after 48 h of in vitro infection. Our data suggest that bosentan-treated mice have a delay in controlling parasitism which is compensated for exacerbated inflammation. Infection is eventually controlled in these animals and lethality is unchanged, demonstrating that ET-1 plays a minor role in the protection against acute murine T. cruzi infection.